A sustainable method of desalination using stacked layer filtration and magnetism - Mohan Venkata Sai Krishna Vellampalli; Prasanna Kuchelar (Desalination and Water Treatment)
Seawater desalination, a promising solution for potable water, faces challenges such as high operational costs, limited durability, and fouling susceptibility that necessitate effective management solutions. This study presents a novel hybrid experimental approach combining magnetic treatment and stacked layer filtration. This study created eight combinations of two-stage treatment using permanent magnets, electromagnets (10 V), and stacked layer filtration to treat artificial seawater (ASW) derived from different salt mixes. The goal was to reduce salinity content rather than relying on brine rejection. It was observed the removal of chloride in all samples, leading to favourable outcomes. Overall, Combinations 2 and 7 consistently perform well across different dilutions, making them the most versatile methods. Combinations 6 and 8 are highly effective in undiluted conditions and moderate dilutions, while pairings 3 and 6 are less reliable, particularly at higher dilutions. Further, it reveals that manual cleaning of fabric filters used in stacked layer filtration removes accumulated salts from evaporation, making them reusable. Furthermore, the conductive graphene sheet showed no signs of swelling. A hybrid combination, such as magnetism and stacked layer filtration, could help address the global water crisis, with continuous testing and development establishing its suitability for various countries and applications.